(untitled) (Journal of Rashid Latif Medical College, 2023)
Background: The prevalence of Helicobacter pylori shows the widevariation among developing and developed countries. The main reasonto higher prevalence in developing countries is their low basic hygiene,poor diet and improper sanitation. All these factors favor to the spreadof H. pylori infection in human population. The prevalence of H. pyloriin a specific area shows the level of hygienist of that area. The mainfocus of study was to estimate the seroprevalence of H. pylori infectionin population of Islamabad.Methods: The study was conducted among 435 clinically suspectedpatients. Samples were collected and serum was separated. H. pylori'One Step Test Device' based on immune-chromatographic techniquewas used for the detection of H. pylori antibodies.Results: In the tested 435 clinically suspected patients, the subjectswere categorized into 2 groups. Male group with 211 patients showed34 positive cases, while 56 females from second group are positive outof 224. The overall percentages revealed 12.87%, females and 7.80%males as H. pylori positive. Overall there are 20.67% positive and79.30% negative cases for H. pylori infection. Conclusion: Thepresent results showed the prevalence of H. pylori in reported area andconfirmed that the prevalence of disease is higher in developingcountries.